MiRNA Profiling: How to Bypass the Current Difficulties in the Diagnosis and Treatment of Sarcomas. (24th January 2011) - Gougelet, Angélique; Perez, Jennifer; Pissaloux, Daniel; Besse, Anthony; Duc, Adeline; Decouvelaere, Anne-Valérie; Ranchere-Vince, Dominique; Blay, Jean-Yves; Alberti, Laurent
Abstract : Sarcomas are divided into a group with specific alterations and a second presenting a complex karyotype, sometimes difficult to diagnose or with few therapeutic options available. We assessed if miRNA profiling by TaqMan low density arrays could predict the response of undifferentiated rhabdomyosarcoma (RMS) and osteosarcoma to treatment. We showed that miRNA signatures in response to a therapeutic agent (chemotherapy or the mTOR inhibitor RAD-001) were cell and drug specific on cell lines and a rat osteosarcoma model. This miRNA signature was related to cell or tumour sensitivity to this treatment and might be not due to chromosomal aberrations, as revealed by a CGH array analysis of rat tumours. Strikingly, miRNA profiling gave promising results for patient rhabdomyosarcoma, discriminating all types of RMS: (Pax+) or undifferentiated alveolar RMS as well as embryonal RMS. As highlighted by these results, miRNA profiling emerges as a potent molecular diagnostic tool for complex karyotype sarcomas.